THE ROLE OF THE INTERNET OF THINGS (IOT) IN CONNECTING DEVICES IN SMART HOMES: A LITERATURE REVIEW ON INTEGRATION, EFFICIENCY, AND SECURITY - Siti Nurhayati; Suhana binti Sarkawi (INJOSEDU: International Journal of Social and Education, 2025)
The development of Internet of Things (IoT) technology has opened up enormous opportunities for interconnecting various devices in smart homes, creating an integrated and efficient ecosystem. This study conducted a literature review to understand the role of IoT in connecting smart home devices, focusing on two main aspects: device integration and efficiency, and system security. The literature analysis shows that the integration of IoT devices enables centralised control and system automation, which improves comfort and energy efficiency. However, security challenges are a major concern due to the potential risks of hacking and privacy violations that could endanger residents. Therefore, the implementation of layered security methods is essential to ensure the protection of data and IoT device systems. In conclusion, IoT plays a significant role in creating smart homes that are not only intelligent and energy-efficient but also safe to use.